2020
DOI: 10.1111/poms.13150
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and Dynamic Promotion Strategies in Crowdfunding with Network Externalities

Abstract: C rowdfunding, a peer-to-peer fundraising mechanism, solicits capital from individual backers to support entrepreneurial projects. Entrepreneurs set a funding target and deadline; the project will be funded only if it reaches this funding target by the deadline. Backers individually decide whether to contribute, but their total contributions collectively determine whether the project will be successfully funded. This study models the dynamics of backers' contributions in the presence of success uncertainty and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Videos also can help introduce projects and give people closer looks at creators' work. Some scholars account empirically for the presence of visual information [14,9,19]. Mollick [1] argues that the inclusion of video signals preparation and higher project quality; in turn, the presence of video is associated with greater crowdfunding success (see also [7,20,6].…”
Section: Number Of Pictures and Videosmentioning
confidence: 99%
“…Videos also can help introduce projects and give people closer looks at creators' work. Some scholars account empirically for the presence of visual information [14,9,19]. Mollick [1] argues that the inclusion of video signals preparation and higher project quality; in turn, the presence of video is associated with greater crowdfunding success (see also [7,20,6].…”
Section: Number Of Pictures and Videosmentioning
confidence: 99%
“…Researchers intensively study network effects of two-sided platforms in recent years. Li et al [23] examine the network effects of backers on crowdfunding projects. Hinz et al [24] propose an influx-outflow model for estimation of network effects on two-sided business-to-consumer (B2C) platforms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While recent operations research has been concentrated on rewards-based (pre-selling) funding (Li et al 2020, Wei et al 2020 or debt-based funding (Lu et al 2020), equity funding has different dynamics (Roma et al 2018). Overall, funders in rewards-based or debt-based do not have to look for guidance in what to fund because they support projects they care about.…”
Section: Equity Crowdfundingmentioning
confidence: 99%
“…This implies that lead investors with a network of followers and experience in assessing startups in a crowdfunding context are essential to a crowdfunding platform's success. These crowdfunding campaigns must ensure that the quality of their offerings is properly communicated (Chakraborty and Swinney 2021), that misconduct of both the startup team and potential investors is effectively policed (Belavina et al 2020), and that the coordination between the startups and their investors is efficiently managed (Li et al 2020). While these activities could all be fulfilled by an experienced lead investor, none of these studies address how high-performing investors can be identified and engaged by the platform as lead investors to improve their funding operations.…”
Section: Identifying High-performance Investorsmentioning
confidence: 99%